A Quantitative Magnetic Resonance Cholangiopancreatography Metric of Intrahepatic Biliary Dilatation Severity Detects High‐Risk Primary Sclerosing Cholangitis. Issue 4 (21st November 2021) - Selvaraj, Emmanuel A.; Ba‐Ssalamah, Ahmed; Poetter‐Lang, Sarah; Ridgway, Gerard R.; Brady, J. Michael; Collier, Jane; Culver, Emma L.; Bailey, Adam; Pavlides, Michael
Abstract : Magnetic resonance imaging with magnetic resonance cholangiopancreatography (MRI‐MRCP) in primary sclerosing cholangitis (PSC) is currently based on qualitative assessment and has high interobserver variability. We investigated the utility and performance of quantitative metrics derived from a three‐dimensional biliary analysis tool in adult patients with PSC. MRI‐MRCP, blood‐based biomarkers, and FibroScan were prospectively performed in 80 participants with large‐duct PSC and 20 healthy participants. Quantitative analysis was performed using MRCP+ (Perspectum Ltd., United Kingdom), and qualitative reads were performed by radiologists. Inter‐reader agreements were compared. Patients were classified into high risk or low risk for disease progression, using Mayo risk score (MRS), Amsterdam‐Oxford model (AOM), upper limit of normal (ULN) alkaline phosphatase (ALP), disease distribution, and presence of dominant stricture. Performance of noninvasive tools was assessed using binomial logistic regressions and receiver operating characteristic curve analyses. Quantitative biliary metrics performed well to distinguish abnormal from normal bile ducts ( P < 0.0001). Interobserver agreements for MRCP+ dilatation metrics (intraclass correlation coefficient, 0.90‐0.96) were superior to modified Amsterdam intrahepatic stricture severity score (κ = 0.74) and Anali score (κ = 0.38). MRCP+ intrahepatic dilatation severity showed excellent performance to classify patients into high‐risk and low‐risk groups, using predictors of disease severity as the reference (MRS, P < 0.0001; AOM, P = 0.0017; 2.2 × ULN ALP, P = 0.0007; 1.5 × ULN ALP, P = 0.0225; extrahepatic disease, P = 0.0331; dominant stricture, P = 0.0019). MRCP+ intrahepatic dilatation severity was an independent predictor of MRS >0 (odds ratio, 31.3; P = 0.035) in the multivariate analysis. Conclusion: Intrahepatic biliary dilatation severity calculated using MRCP+ is elevated in patients with high‐risk PSC and may be used as an adjunct for risk stratification in PSC. This exploratory study has provided the groundwork for examining the utility of novel quantitative biliary metrics in multicenter studies. Abstract : image